Hubungan Tingkat Pengetahuan Dengan Kepatuhan Minum Obat Pada Pasien Tuberkulosis Paru Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2025 - Yosril Bahendra; Murwati Murwati; Sulastri Sulastri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is one of the 10 leading causes of death worldwide (Andriani et al., 2023). Indonesia ranks second in terms of cases after India. In 2024, the number of tuberculosis cases detected reached 885,000, with a distribution of 496,000 in males, 359,000 in females, and 135,000 in children aged 0–14 years. The purpose of this study was to determine the relationship between knowledge and medication adherence among pulmonary tuberculosis patients in the Telaga Dewa Community Health Center (Puskesmas) in Bengkulu City in 2025. The method used was a cross-sectional study, with data collected using a questionnaire. The population in this study were 37 pulmonary tuberculosis patients undergoing treatment. Data were analyzed bivariately using the Chi-Square test with a significance level of α = 0.05. The univariate analysis of knowledge showed that the majority of respondents (23 respondents) had good knowledge, 62.2%. Compliance was also found in the majority of respondents (64.9%). The statistical test yielded a p-value of 0.000, concluding that there is a relationship between knowledge and medication adherence in pulmonary tuberculosis patients in the Telaga Dewa Community Health Center, Bengkulu City, in 2025. The researchers recommend that the Community Health Center improve health education and medication monitoring to improve knowledge and medication adherence in pulmonary tuberculosis patients, thus achieving optimal treatment success.